A Review of DNA Vaccines Against Influenza - Lee, Leo Yi Yang; Izzard, Leonard; Hurt, Aeron C. (Frontiers in Immunology, 2018)
The challenges of effective vaccination against influenza are gaining more mainstream attention, as recent influenza seasons have reported low efficacy in annual vaccination programs worldwide. Combined with the potential emergence of novel influenza viruses resulting in a pandemic, the need for effective alternatives to egg-produced conventional vaccines has been made increasingly clear. DNA vaccines against influenza have been in development since the 1990s, but the initial excitement over success in murine model trials has been tempered by comparatively poor performance in larger animal models. In the intervening years, much progress has been made to refine the DNA vaccine platform—the rational design of antigens and expression vectors, the development of novel vaccine adjuvants, and the employment of innovative gene delivery methods. This review discusses how these advances have been applied in recent efforts to develop an effective influenza DNA vaccine.